2016
DOI: 10.18632/oncotarget.13797
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63α and microRNAs: leveraging the epithelial-mesenchymal transition

Abstract: The epithelial-mesenchymal transition (EMT) is a cellular reprogramming mechanism that is an underlying cause of cancer metastasis. Recent investigations have uncovered an intricate network of regulation involving the TGFβ Wnt, and Notch signaling pathways and small regulatory RNA species called microRNAs (miRNAs). The activity of a transcription factor vital to the maintenance of epithelial stemness, ?Np63a, has been shown to modulate the activity of these EMT pathways to either repress or promote EMT. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 135 publications
1
13
0
Order By: Relevance
“…We previously showed that TP63 controls the expression of high-molecular weight keratins (KRT5, KRT6, and KRT14) and suppresses EMT (Choi et al, 2014b; Tran et al, 2013). The central role of p63 in the maintenance of epithelial phenotype and EMT was confirmed in several variants of solid tumors (Soares and Zhou, 2018; Stacy et al, 2017; Tanaka et al, 2018). We therefore performed additional analyses to further characterize the role of EMT in SARC.…”
Section: Resultsmentioning
confidence: 88%
“…We previously showed that TP63 controls the expression of high-molecular weight keratins (KRT5, KRT6, and KRT14) and suppresses EMT (Choi et al, 2014b; Tran et al, 2013). The central role of p63 in the maintenance of epithelial phenotype and EMT was confirmed in several variants of solid tumors (Soares and Zhou, 2018; Stacy et al, 2017; Tanaka et al, 2018). We therefore performed additional analyses to further characterize the role of EMT in SARC.…”
Section: Resultsmentioning
confidence: 88%
“…NSC and sip63 samples clustered together with up- or down-regulation of a majority of miRNA correlating with sample type. This list of miRNA was compared to a previously published dataset of p63-regulated miRNAs summarized in our previous study 21 . Eight of the currently identified miRNA were previously shown to be regulated by ΔNp63α and served as positive controls (miR-185–5p, miR-205-5p, miR-130b-3p, miR-203a-5p, and miR-429) 10 , 22 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has indicated that miR-373 participates in tumor metastasis (32), and the role of human miR-373 in metastasis is dependent the tissue and organ type. miR-373 was first identified to be a metastasis-promoting miRNA in breast cancer (30).…”
Section: Discussionmentioning
confidence: 99%